2015
DOI: 10.1111/pedi.12252
|View full text |Cite
|
Sign up to set email alerts
|

Achieving International Society for Pediatric and Adolescent Diabetes and American Diabetes Association clinical guidelines offers cardiorenal protection for youth with type 1 diabetes

Abstract: Objective Most youth with type 1 diabetes do not meet the American Diabetes Association (ADA) and International Society for Pediatric and Adolescent Diabetes (ISPAD) targets for HbA1c, blood pressure, lipids, and BMI. We hypothesized that ISPAD/ADA goal achievement at baseline would be associated with cardiorenal risk factors at baseline and 2 year follow-up in adolescents with type 1 diabetes. Methods We assessed the cross-sectional and longitudinal relationships between ISPAD/ADA goal achievement at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…The Determinants of Macrovascular Disease in Adolescents with Type 1 Diabetes study was initiated to investigate atherosclerotic disease risk in youth with T1D [13, 14]. The study enrolled 300 subjects 12–19 years old from 2008 to 2010, with type 1 diabetes and 100 non-diabetic controls of similar age [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Determinants of Macrovascular Disease in Adolescents with Type 1 Diabetes study was initiated to investigate atherosclerotic disease risk in youth with T1D [13, 14]. The study enrolled 300 subjects 12–19 years old from 2008 to 2010, with type 1 diabetes and 100 non-diabetic controls of similar age [13].…”
Section: Methodsmentioning
confidence: 99%
“…The study enrolled 300 subjects 12–19 years old from 2008 to 2010, with type 1 diabetes and 100 non-diabetic controls of similar age [13]. Study participants with T1D were diagnosed by islet cell antibody or by provider clinical diagnosis, had diabetes duration >5 years at entry into the study, and received care at the Barbara Davis Center for Childhood Diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in type 1 diabetes (T1D) (1, 2) with abnormalities measurable in adolescence (3). In T1D youth we have reported an inverse relationship between insulin sensitivity (IS) and peak exercise capacity (VO 2 peak) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Measures of arterial stiffness including pulse wave velocity (PWV), augmentation index (AIx) and brachial distensibility (BrachD) have been shown to predict future CVD and all-cause mortality [2426] (Table 1). In adolescents with type 1 diabetes, we recently reported an inverse relationship between achieving International Society of Pediatric and Adolescents Diabetes’ targets for HbA1c, LDL-C, HDL-C, TG, BMI and BP and arterial stiffness (measured by PWV, AIx and BracD) [28]. Furthermore, we have shown that apoB is strongly associated with arterial stiffness by PWV in adolescents with type 1 diabetes, and that measurement of apoB in addition to LDL-C may be helpful in stratifying CVD-risk in adolescents with type 1 diabetes and borderline LDL-C (100–129mg/dL) [29].…”
Section: Macrovascular Diseasementioning
confidence: 99%